Respuesta :

Answer:

The comparison graph is also attached in 3rd figure. In the 3rd figure, the graph with vertex (0, 0) is representing [tex]f(x) = x^2[/tex] and [tex]\:f\left(x\right)=\left(x-6\right)^2[/tex] is represented as being shifted 6 units to the right as compare to the function [tex]f(x) = x^2[/tex].

Step-by-step explanation:

When we Add or subtract a positive constant, let say c, to input x, it would be a horizontal shift.  

For example:

Type of change               Effect on y = f(x)

[tex]y = f(x - c)[/tex]                      horizontal shift: c units to right

So

Considering the function

[tex]f(x) = x^2[/tex]

The graph is shown below. The first figure is representing [tex]f(x) = x^2[/tex].

Now, considering the function

[tex]\:f\left(x\right)=\left(x-6\right)^2[/tex]

According to the rule, as we have discussed above, as a positive constant 6 is added to the input, so there is a horizontal shift, 6 units to the right.

The graph of [tex]\:f\left(x-6\right)=\left(x-6\right)^2[/tex] is shown below in second figure. It is clear that the graph of  [tex]\:f\left(x-6\right)=\left(x-6\right)^2[/tex]  is shifted 6 units to the right as compare to the function [tex]f(x) = x^2[/tex].

The comparison graph is also attached in 3rd figure. In the 3rd figure, the graph with vertex (0, 0) is representing [tex]f(x) = x^2[/tex] and [tex]\:f\left(x\right)=\left(x-6\right)^2[/tex] is represented as being shifted 6 units to the right as compare to the function [tex]f(x) = x^2[/tex].

Ver imagen SaniShahbaz
Ver imagen SaniShahbaz
Ver imagen SaniShahbaz